2006
DOI: 10.1111/j.1439-0264.2005.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratum adiposum, A Special Structure of the African Catfish Skin (Clarias gariepinus, Burchell 1822)

Abstract: The skin histology of Clarias gariepinus, a scaleless teleost from south central Africa, is described. The African catfish epidermis is composed of epithelial cells representing 62.3% of volumetric density (Vv), club cells (Vv = 25.7%), mucous cells (Vv = 10.5%) and melanocytes (Vv = 1.4%). Its thickness amounts to approximately 240 microm. The dermis is distinguished by two well differentiated layers, the stratum adiposum, containing prominent amounts of adipose tissue, which forms large, oblong compartments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
0
20
0
3
Order By: Relevance
“…We have here demonstrated that club cells are indeed present in high density in the skin of the jundiá, that these cells are large and rounded, and located in the middle of the stratified epithelium. Interestingly, club cells of R. quelen are binucleated, as has been found for other catfishes (e.g., Chapman & Johnson, 1997;Smith, 2000;Guerra et al, 2006;Damasceno et al, 2012) suggesting an intense cell metabolic activity; the significance of this finding, however, remains to be clarified.…”
Section: Concentration Of Skin Homogenatementioning
confidence: 54%
See 1 more Smart Citation
“…We have here demonstrated that club cells are indeed present in high density in the skin of the jundiá, that these cells are large and rounded, and located in the middle of the stratified epithelium. Interestingly, club cells of R. quelen are binucleated, as has been found for other catfishes (e.g., Chapman & Johnson, 1997;Smith, 2000;Guerra et al, 2006;Damasceno et al, 2012) suggesting an intense cell metabolic activity; the significance of this finding, however, remains to be clarified.…”
Section: Concentration Of Skin Homogenatementioning
confidence: 54%
“…In Characiformes, which features the largest number of species assessed in this context, alarm responses to alarm cells substances have been reported, for example, in Brycon amazonicus (Honda et al, 2008); Brycon cephalus (Ide et al, 2003); Gymnocharacinus bergi (Cordi et al, 2005); Leporinus macrocephalus (Alves et al, 2013); Leporinus piau ; Mimagoniates lateralis and M. microlepis (Duboc, 2007), and Piaractus mesopotamicus (Jordão & Volpato, 2000). In the Siluriformes, the second order most studied in this context, six species have been evaluated: Arius felis (e.g., Smith 2000), Clarias gariepinus (e.g., Guerra et al, 2006;van de Nieuwegiessen et al, 2008;van de Nieuwegiessen et al, 2009), Ictalurus punctatus (e.g., Chapman & Johnson, 1997;Valentic & Caprio, 1994), Pimelodella lateristriga (e.g., Damasceno et al, 2012), Pseudoplatystoma corruscans (e.g., Giaquinto & Volpato, 2001). However, only two studies were found about the role of epithelial alarm cells on behavioral responses in jundiá, R. quelen.…”
Section: Discussionmentioning
confidence: 99%
“…In the ariid catfish Plicofollis argyropleuron (Valenciennes 1840) it is described as elongated ( Arius tenuispinis species cited in [4], whereas in Ariopsis felis (Linnaeus 1766) is globular (species Arius felis as cited in [31]. In the bullhead Coreobagrus brevicorpus (Mori 1936) this cell type shape varies from globular to elongated (cited as Pseudobagrus brevicorpus in [7], being elongated in the African sharptooth catfishes Clarias gariepinus (Burchell 1822) [3] and Clarias batrachus (Linnaeus 1758) [45], and globular in Ictalurus punctatus (Rafinesque 1818) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal cells, also known as filament containing cells, are the smallest and most numerous cells, being the major epithelium covering cells, and are found all over the epiderm, from basal to superficial layers [1], [3]. Mucous and granular cells are conspicuous round cells with peripheral flattened nucleus, located on the apical region of the epithelium [1].…”
Section: Introductionmentioning
confidence: 99%
“…The scale‐less African catfish Clarias gariepinus (Burchell) was chosen for its tolerance to high and low temperatures, which makes it a good model to study temperature effects on wound healing. The microscopic structure of the epidermis and dermis was described by Guerra et al (2006). Here, the kinetics of the cutaneous cicatrization in C. gariepinus at 30° C, both at the macroscopic and microscopic level, was studied.…”
Section: Introductionmentioning
confidence: 99%